Diversity of Exopolysaccharide Producing Fungi from Foot Hills of Shivalik Ranges of Chandigarh Capital Region - Yadava, Kanchan Lata; K. Rahi, Deepak; K. Soni, Sanjeev; Rahi, Sonu (Research in Biotechnology, 2012)
In this investigation, the diversity of exopolysaccharide producing fungi of foot hills of Shivalik ranges of Chandigarh capital region have been studied. The study resulted in isolation of a total of 94 fungal isolates of which 52 isolates belonging to 17 different genera viz., Agaricus, Alternaria, Aspergillus, Aureobasidium, Candida, Curvullaria, Chaetomium, Fusarium, Ganoderma, Penicillium, Pleurotus, Polyporous, Rhizopus, Saccharomyces, Stemophylium, Termitomyces, and Tricholoma etc. were found to possess the EPS producing potential. These isolates have been categorized into five different groups on the basis of the EPS quantities they produced. These included Group I with production range of : > 1g/l ; Group II with production range of : 1-2 g/l ; Group III with production range of : 2-3 g/l ; Group IV with production range of : 3-4 g/l and Group V with production range of : 4-5 g/l. Out of these 52 EPS producing isolates, 11 were found to be the prominent producers with Auerobasidium RYLF 10 as the most potential isolate with EPS concentration of 4.60g/l followed by the species of Penicillium RYLF 35, Aspergillus RYLF 17 and Ganoderma RYMF 15. No correlation between EPS concentration and the biomass yield could be traced.